2000
DOI: 10.21061/jots.v26i2.a.6
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Strategic Thinking of Novice Designers: Discontinuity Between Theory and Practice</p>

Abstract: IntroductionIn two studies we conducted, untutored Grade 7 students produced solutions to a design-and-make task in ways significantly different than ones prescribed by many textbooks and theories about learning to design. We found that novice designers (a) sequence the subprocesses of designing quite differently than the prescribed models, (b) do not generate several possible solutions and choose the most effective, (c) make greater use of three-dimensional modeling, (d) use less two-dimensional modeling than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Although research studies addressing children's engagement with design technology (e.g., MacDonald and Gustafson 2004) provide some insights into their abilities, the findings have been mixed. For example, some studies have questioned whether children should even be engaged in design drawing as they would rather experiment with materials instead (e.g., Welch and Lim 2000). Other research (e.g., MacDonald and Gustafson 2004) has even suggested that it is unnatural for young students to develop designs until their drawing skills are more developed.…”
Section: Design Construction Evaluation and Redesignmentioning
confidence: 99%
“…Although research studies addressing children's engagement with design technology (e.g., MacDonald and Gustafson 2004) provide some insights into their abilities, the findings have been mixed. For example, some studies have questioned whether children should even be engaged in design drawing as they would rather experiment with materials instead (e.g., Welch and Lim 2000). Other research (e.g., MacDonald and Gustafson 2004) has even suggested that it is unnatural for young students to develop designs until their drawing skills are more developed.…”
Section: Design Construction Evaluation and Redesignmentioning
confidence: 99%
“…The diversity of available learning models, and the variances and congruencies among them, suggest that there are probably many different kinds of learning, between and within individuals, as there are many different teaching-learning strategies (Phillips and Soltis, 2004). Welch and Lim (2000) found in their study that significant differences existed between the strategies used by novice designers and the theoretical models contained in many textbooks and curriculum documents, suggesting that teachers must think carefully about the way in which students are expected to explore, develop, and communicate their design proposals, and that teaching any form of linear design process may be counter-productive to students' success in developing a solution to a design-and-make task. Engagements with the real world, Griffiths (2003), have been used by some vocational institutions, and include pre-post and post-only competency tests.…”
Section: Figure 1: Carpet Diagram Of the Learning Continuum (Modifiedmentioning
confidence: 99%
“…Two of the coding schemes (Welch & Lim, 2000;Wilson, Smith, & Householder, 2013) adopt what is referred to in this study as a general engineering design process (GEDP) model to document the amount of time students perform each of the steps. Though both coding schemes were identified by their authors as being grounded in research related to engineering design, both were also crafted with the intent of being used by teachers as a scaffolding tool for students.…”
Section: Focus and Intentmentioning
confidence: 99%
“…In addition to the number of codes, Table 2 illustrates there are differences in the nature of codes attempting to illustrate students cognitive activity. Whereas one coding scheme applies codes to describe students reasoning around the three domains of function, structure, and behavior (Wells et al, 2014), other coding schemes (Welch & Lim, 2000;Wilson et al, 2013) use codes illustrating more of a linear model of designing (e.g. such as identify a need or a problem, research a need or problem, and model a possible solution).…”
Section: Codes Employedmentioning
confidence: 99%
See 1 more Smart Citation